Analisis Keterampilan Menulis Deskripsi Siswa Kelas VI SDN 2 Worawari - Tyaningrum, Melinda Adi; Suryatin, Suryatin; Purnamasari, Mega Isvandiana (PGSD STKIP PGRI Pacitan, 2022)
This study aims to determine: (1) the descriptive writis skill of grade VI students in SDN 2 Worawari; (2) the obstacles faced by students in writing descriptive reset. This type of the research was descriptive qualitative. This research war conducted in the second semester of the 2019/2020 in academic year of subjects were 23 grade VI students of SDN 2 Worawari. Data collection used test methods, and interviews. The validity of the data used technical triangulation. The data analysis technique in this study used Miles and Hubberman.The results of this study indicate that the writing skills of grade VI students of SDN 2 Worawari were 26% in the high category, 39% in the medium category, and 34% in the low category. The obstacles faced by students in writing descriptive were students still found difficulties to put ideas into words or sentences, and in correct spelling and punctuation.